If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 7 = 8n + -13 Reorder the terms: 7 + 6n = 8n + -13 Reorder the terms: 7 + 6n = -13 + 8n Solving 7 + 6n = -13 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 7 + 6n + -8n = -13 + 8n + -8n Combine like terms: 6n + -8n = -2n 7 + -2n = -13 + 8n + -8n Combine like terms: 8n + -8n = 0 7 + -2n = -13 + 0 7 + -2n = -13 Add '-7' to each side of the equation. 7 + -7 + -2n = -13 + -7 Combine like terms: 7 + -7 = 0 0 + -2n = -13 + -7 -2n = -13 + -7 Combine like terms: -13 + -7 = -20 -2n = -20 Divide each side by '-2'. n = 10 Simplifying n = 10
| F(20)=b | | 9x+2=25x+8 | | 6t+3t=6 | | 10x+3=7x-39 | | -2(x+11)=6 | | .25y+3=-5 | | 5x+1=-2-8 | | -2.89=1.7 | | 6y+3(5y-19)-(y+2)=-142 | | 10=3+2 | | 24=-6m | | 0.25+.20x+1=2.25 | | F(a)=20 | | 2(x+2)-3(2x+5)=5 | | 7d=14 | | 2+3(p+3)=21 | | 3x-2=44 | | 4g+4=2g+12 | | 4b^2-49g^2=0 | | x^3+7x^2-25x-150=x^2 | | .50x+.50x=x+1 | | (4x+2)-(12x+8)+10x-3=6+11 | | 8x-1=2x-37 | | 4=2(y-5)-2 | | .4x-9=-7 | | (2x-7)(4x+12)=0 | | 5T=2T-12 | | 22+4x-14=0 | | -5.5=t+2 | | f(10)=100.3 | | 8x-3=4x+21 | | 3(2x-3)+3(3)=-7x |